Web-Based Tracer Study Information System Development Using Rapid Application Development for Alumni Data Management in FMIPA UNSRAT - Timothy Salomo Van Dijken Boediman; Chriestie Ellyane Juliet Clara Montolalu; Dodisutarma Lapihu; Mahardika Inra Takaendengan; Mans Lumiu Mananohas; Rillya Arundaa (Universitas Teknokrat Indonesia, 2025)
Tracer studies are essential tools for evaluating the relevance and quality of higher education curricula, as they facilitate the tracking of alumni career outcomes. However, the conventional utilization of Google Forms for data collection in the Information Systems Study Program at FMIPA UNSRAT has led to fragmented and inefficient alumni data management. The objective of this research is to develop a web-based tracer study information system to enhance the efficiency and accuracy of alumni data management. The system's development employed the Rapid Application Development (RAD) method, which prioritizes iterative prototyping and active stakeholder involvement. The research process entailed a multifaceted approach, encompassing a needs analysis, system design, implementation, and black-box testing to ensure system reliability. The resulting web-based system enables alumni to complete dynamic questionnaires according to their employment status, while administrators can efficiently manage and visualize alumni data through interactive dashboards. The system's structured data collection and visualization features support program evaluation and accreditation processes. Preliminary testing results indicate that the system functions as intended and significantly enhances the management and utilization of alumni data. The present study demonstrates that the integration of RAD and web-based technology provides a practical solution for tracer study implementation in higher education institutions.